PERSEPSI GURU PENDIDIKAN AGAMA ISLAM TERHADAP PENGGUNAAN APLIKASI TIKTOK SEBAGAI MEDIA PEMBELAJARAN DI SDN 14 LAKUDO KABUPATEN BUTON TENGAH - Sopiah, Sopiah; La Jusu; Basri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine Islamic Religious Education (PAI) teachers' perceptions of TikTok as a learning medium and to analyze how those perceptions manifest in classroom practice at SDN 14 Lakudo, Buton Tengah Regency. Employing a qualitative approach with a case study design, data were collected through in-depth interviews, participant observation, and documentation involving two PAI teachers. Data analysis followed the interactive model of Miles et al., supported by source triangulation and member checking to ensure validity. The findings reveal that both teachers hold a positively critical perception of TikTok as a learning medium, recognizing its significant potential to enhance student engagement and learning motivation through short-form video content. However, this positive stance is consistently accompanied by heightened awareness of the risks posed by negative content that may undermine Islamic moral values. Consequently, teachers' perceptions directly shape their pedagogical practice through rigorous content selection, active supervision, and value reinforcement during every TikTok-integrated lesson. This study concludes that teacher perception, rather than institutional infrastructure, serves as the primary driver of effective and values-based digital media integration in Islamic religious education, contributing meaningfully to SDG 4 on quality education and SDG 16 on strong and accountable institutions.